Influence of tree species on improvement of soil fertility status in central zone of Punjab - Singh, Baljit; Sharma, K.N.; Kumar, Dinesh (Indian Journal of Agroforestry, 2020)
Litterfall added by trees improves the properties of soil under the trees. The influence of three tree species was assessed on soil organic carbon (QC), available macro (N, P and K) and micronutrients (Zn, Fe, Mn and Cu) in the soil profile. Depthwise (0-15, 15-30, 30-60, 60-90 and 90-120 cm) soil samples were analysed from 10 year old Melia azedarach (dek) at site 1 (spacing 3 x 2 m), Dalbergia sissoo (shisham) (single line, 3 m) and Eucalyptus tereticornis (eucalyptus) (2 x 2 m) at site 2 and adjoining open areas (controls) at research farm of Punjab Agricultural University, Ludhiana. Dek and eucalyptus have higher diameter at breast height (15.1 and 13.8 cm, respectively) and height (13.3 and 16.6 m, respectively) than shisham. The concentration and accumulation of soil QC and available nutrients were higher under trees than control. The soil QC and nutrient concentration decreased with increase in depth irrespective of tree species. Soil QC increased by 92.7% under dek over control (3.10 g/kg) in the surface soil layer at site 1 whereas at site 2, the increase over control (2.91 g/kg) was higher under eucalyptus (82.6%) than shisham (45.2%). The QC content in the 0-120 cm soil profile was higher under trees (32.5 to 39.7 Mg/ha) than control (27.2 and 29.2 Mg/ha) at both the sites. The available N, P and K contents were the highest under dek at site 1 and eucalyptus at site 2 in the surface as well as 0-120 cm soil profile. The micronutrient accumulation in soil profile was also higher under the tree species as compared to control. Available micronutrients were significantly higher under dek and eucalyptus than shisham and control at the respective sites.